Scientific and technical guidance for the preparation and presentation of a dossier for evaluation of an infant and/or follow‐on formula manufactured from protein hydrolysates (Revision 1). (26th March 2021) - ; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Endorsement date 21 January 2021 Implementation date 27 March 2021 Following a request from the European Commission, EFSA was asked to provide scientific and technical guidance for the preparation and presentation of a dossierfor evaluation of an infant and/or follow‐on formula manufactured from protein hydrolysates. This guidance document addresses the information and data to be submitted to EFSA on infant and follow‐on formulae manufactured from protein hydrolysates with respect to the nutritional safety and suitability of the specific formula and/or the formula's efficacy in reducing the risk of developing allergy to milk proteins. The guidance will be further reviewed and updated with the experience gained from the evaluation of specificdossiers, and in the light of applicable Unionguidelines and legislation. The guidance was adopted by the Panel on Dietetic Products, Nutrition and Allergies on 5 April 2017.Upon request from the European Commission in 2020, it has been revised to inform food business operators of the new provisions in the pre‐submission phase and in the procedure set out in the General Food Law, as amended by the Transparency Regulation. This revised guidance applies to all dossiers submitted as of 27 March 2021 and shall be consulted for the preparation of dossiers intended to be submitted from that date onwards. For dossiers submitted prior to 27 March 2021, the previous guidance, published in May 2017 remains applicable.